2015
DOI: 10.7592/ejhr2015.3.1.marone
|View full text |Cite
|
Sign up to set email alerts
|

Online humour as a community-building cushioning glue

Abstract: This article examines the uses and functions of humour in an online

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Baym (1995) advanced that a friendly social context was created despite the impersonal elements of the medium. Marone (2015) analyzed the discursive functions of humor in natural online interactions where participants presented, discussed, and criticized user-generated artifacts. The study revealed that humor was identified through linguistic tools including lexical selection, capitalization, wordplay, extreme case formulations, and emoticons.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Baym (1995) advanced that a friendly social context was created despite the impersonal elements of the medium. Marone (2015) analyzed the discursive functions of humor in natural online interactions where participants presented, discussed, and criticized user-generated artifacts. The study revealed that humor was identified through linguistic tools including lexical selection, capitalization, wordplay, extreme case formulations, and emoticons.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These accessible and integrated game design toolkits prompt a convergence of roles between players and creators ("playators," cfr. Marone, 2015b), which allows users to express their creativity through playful design (see Fig. 5).…”
Section: Game Design As Editingmentioning
confidence: 99%
“…Others have looked at, for example, students' oral vocabulary and writing skills development (Golonka, Tare, & Bonilla 2017;Lai, 2016;Reynolds & Anderson, 2015), the interaction between text and video (Hung & Higgins, 2016), and social and cognitive presence in chats (Wang et al, 2016). Expressions of empathy (Pfeil & Zaphiris, 2007) and humor (Marone, 2015) have also been studied. Räsänen and Muhonen (2020b) focused on community building in Finnish language learners' Padlet chat: While students shared glimpses of their everyday lives and commented on each other's language productions, they also discussed belonging to a supportive community of learners.…”
mentioning
confidence: 99%